2023
DOI: 10.1302/2046-3758.122.bjr-2022-0116.r1
|View full text |Cite
|
Sign up to set email alerts
|

What outcomes have been reported on patients following open lower limb fracture, and how have they been measured?

Abstract: AimsOpen lower limb fracture is a life-changing injury affecting 11.5 per 100,000 adults each year, and causes significant morbidity and resource demand on trauma infrastructures. This study aims to identify what, and how, outcomes have been reported for people following open lower limb fracture over ten years.MethodsSystematic literature searches identified all clinical studies reporting outcomes for adults following open lower limb fracture between January 2009 and July 2019. All outcomes and outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Information gathering. A systematic review describing outcomes reported in the literature has been previously published; 5 Outcome headings and themes from the systematic review and qualitative analysis, respectively, were brought together to create the inventory of outcomes for open lower limb fracture. The resulting inventory of outcomes consisted of a long list of 150 outcomes categorized using the COMET taxonomy of outcomes to 3 for a schematic of results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information gathering. A systematic review describing outcomes reported in the literature has been previously published; 5 Outcome headings and themes from the systematic review and qualitative analysis, respectively, were brought together to create the inventory of outcomes for open lower limb fracture. The resulting inventory of outcomes consisted of a long list of 150 outcomes categorized using the COMET taxonomy of outcomes to 3 for a schematic of results.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes important to healthcare professionals and researchers were identified using a systematic literature review to collect, summarize, and categorize contemporary outcomes reported in clinical studies on skeletally mature patients following open lower limb fracture over ten years from 2009. 5 Outcomes important to patients were identified through a secondary thematic analysis of 25 in-depth interview transcripts that explored the lived experience of recovery following open lower limb fracture. Interview participants were recruited as part of the WOLLF HTA-10/57/20 trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,21 A recent study of outcomes following open fractures determined that the domains that are important to patients and should therefore be included in a core outcome set for open fractures include 'Walking, gait and mobility', 'Being able to return to life roles', 'Pain or discomfort' and 'Quality of life'. 22 Using COSMIN methodology, this group of six patients, eight healthcare professionals and 11 research methodologists went on to recommend that the EQ-5D five-level (5L) and LEFS should be used in future research trials, audit and clinical assessment, of open fractures. 23 The current study employed both EQ-5D and LEFS, and though it does not include open fractures, TPFs in the elderly are considered complex fractures according to the NICE definition (joints broken into multiple pieces), 4 and it is reasonable to assume that similar domains are important to patients.…”
Section: Variablementioning
confidence: 99%